Impact of perioperative enteral nutrition on postoperative acute muscle wasting in gastric cancer: a prospective exploratory study with a historical control group - Xing Zeng; Xing Zeng; Xuan Ni; Zhili Shen; Dong Yang; Yajing Gu; Ai Li; Hui Liu; Changdi Li (Frontiers in Oncology, 2025)
ObjectiveAssessing the impact of perioperative enteral nutrition (EN) on postoperative acute muscle atrophy following radical gastrectomy for gastric cancer(GC) (with changes in skeletal muscle mass as the primary outcome indicator).MethodsPatients who underwent GC surgery at the Department of Gastrointestinal Oncology Surgery in a top-tier hospital in Nanjing were selected for the study. The control group, consisting of patients treated between January and June 2023, received routine perioperative nutritional management. The experimental group, consisting of patients treated between July and December 2023, followed a preoperative combined with early postoperative EN program. skeletal muscle mass, grip strength, 6-meter walk test speed, and body weight were compared between the two groups 7 d postoperatively.ResultsThe intervention significantly reduced the loss of skeletal muscle mass, grip strength, and body weight from baseline (p<0.01). However, no significant differences in 6-meter walk test speed were observed between the two groups. After adjusting for confounding factors such as age, gender, nutritional risk screening 2002(NRS 2002) score, education level, diabetes comorbidity, tumor staging, surgical approach, intraoperative blood loss, and operation time, multivariate linear regression analysis showed that the EN program independently influenced the loss rates of skeletal muscle mass, grip strength, and body weight (p<0.01).ConclusionThe perioperative EN program for GC developed in this study enables medical staff to efficiently gather relevant information, providing a more comprehensive and holistic approach to EN for GC patients. The program effectively reduces postoperative acute muscle wasting, grip strength loss, and weight loss. This study provides a reference for clinical perioperative EN management in GC patients.